Effect of Different Radiation Times on the Antibacterial Ability of Laser Diodes (650 nm) on Streptococcus mutans - Sri Kunarti; S. Sukaton; Ajeng Hayyuning Citrasari (Conservative Dentistry Journal, 2019)
Background: Streptococccus mutans is an acid-producing gram-positive bacterium that colonizes the tooth surface and causes damage to the hard tissue of the tooth. S. mutans is known as the main agent that causes caries. Photodynamic therapy (PDT) consisting of photosensitizers and a light source, such as a laser beam, is considered to have an antibacterial effect on S. mutans. However, the factors that influence the antibacterial effects of the lasers, such as the amount of energy, wavelength, use of photosensitizer, and the duration of radiation still need to be studied. Aim: To determine the effective time(duration) of 650 nm laser diode radiation as an antibacterial agent against S. mutans after 30, 45, 60, and 75 seconds of radiation. Method: 30 samples were divided into 6 groups; (1) S. mutans without methylene blue (MB) and laser, (2) S. mutans with MB, but without a laser, (3) S. mutans with MB and laser for 30 seconds, (4) 45 seconds, (5) 60 seconds, and (6) 75 seconds. After treatment, all samples were cultured and incubated for 48 hours then colony counts were carried out in each group. The results were analyzed using ANOVA and Tukey HSD Test with a p value of <0.05. Results: The ANOVA and Tukey HSD test showed a significant difference in each group. Conclusion: 650 nm laser diode radiation with a duration of 75 seconds is an effective time as an antibacterial against S. mutans compared to 30, 45 and 60 seconds.